PERANCANGAN & PENGEMBANGAN SISTEM INFORMASI PROSES SERTIFIKASI PADA LEMBAGA SERTIFIKASI INKINDO MENGGUNAKAN METODE PROTOTYPE - Bayu Nur Khomeini; Muhammad Feizal (CV. Multi Kreasi Media, 2024)
The rapid progress in the field of information technology has had a major impact on various aspects of human life. The most obvious influence is seen in the fundamental changes to the way people conduct transactions, especially in the business world. How to design a web-based certification information system that can simplify, speed up and increase control over the certification process. This research method uses the Research and Development (R&D) method and the system design and development method used in this research is the prototype method. In the implementation of this certification system, the PHP programming language is used, with the CodeIgniter framework and the database used is MySQL. Based on the results of the study, it can be concluded that this system is used to handle the certification process at the Lembaga Sertifikasi INKINDO, this system can also generate reports on the progress of certification.